Global research trends in bone tumors: a bibliometric analysis of medical imaging - Zhou, Yi; Yang, Kaixiang; Cui, Wei (Frontiers in Oncology, 2025)
BackgroundBone tumors, due to their high rate of misdiagnosis, pose significant clinical challenges in diagnosis and treatment. Medical imaging plays a critical role in the accurate detection, staging, and monitoring of these tumors. Understanding global research trends in this area is crucial to advance diagnostic techniques and therapeutic strategies.MethodsThis study performed a comprehensive bibliometric analysis of publications related to bone tumors and medical imaging from 1995 to 2024. Data were retrieved from the Web of Science Core Collection, and keyword co-occurrence analysis, citation patterns, and publication trends were examined to identify research hotspots and emerging trends.ResultsOur analysis shows a steady increase in the number of publications over the past two decades, with the USA leading with 1,258 publications. The University of Texas System ranks first among institutions with 268 publications, while Skeletal Radiology has published the most articles in this field, with 232 publications. Asif Saifuddin is the most prolific author, having published 26 papers. Key research themes include advancements in imaging modalities, bone metastasis, and artificial intelligence (AI) in imaging. Emerging research hotspots include multimodal imaging studies and AI-assisted diagnosis, which are expected to be key areas of future research.ConclusionThis bibliometric study provides a comprehensive overview of medical imaging research in bone tumors. Multimodal imaging approaches and AI-driven tools for early detection, treatment monitoring, and personalized therapy present promising pathways to enhance patient care in the management of bone tumors.